Before I was like a tarzan. but now, I take a pause": mixed methods feasibility study of the Naungan Kasih parenting program to prevent violence against children in Malaysia - Juhari, R.; Yaacob, S. N.; Stuer, F.; Zinser, P.; Kahar, R.; Mansor, M.; Madon, Z.; Arshat, Z.; Nadzri, F. Z. M (BioMed Central, 2023)
Background: espite impressive strides in health, social protection, and education, children continue to experience high rates of child maltreatment in Malaysia. This mixed-methods study assessed the feasibility of a five-session, social learning-based parenting program delivered by government staff in a community setting to reduce violence against children. Methods: Parents of children from birth to 17 years were recruited from two communities near Kuala Lumpur to participate in the government-run program called the Naungan Kasih Positive Parenting Program (“Protecting through Love” in Bahasa Melayu). Quantitative data from female caregivers (N = 74) and children ages 10–17 (N = 26) were collected along with qualitative interviews and focus groups with parents, children, and facilitators. The primary outcome was child maltreatment with secondary outcomes including neglect, positive parenting, acceptability of corporal punishment, harsh parenting, positive discipline, and child behavior problems. Multilevel Poisson regression and multilevel linear regression were conducted to compare baseline and post-test outcomes. Qualitative interviews and focus groups examined how participants experienced the program utilizing a thematic analysis approach. Results: Quantitative analyses found pre-post reductions in overall child maltreatment, physical abuse, emotional abuse, attitudes supporting corporal punishment, parent sense of inefficacy, and child behavior problems. There were no reported changes on positive and harsh parenting, parental mental health, and marital satisfaction, nor were there any other significant changes reported by children. Qualitative findings suggested that the program had tangible benefits for female caregivers involved in the program, with the benefits extending to their family members.